2014
DOI: 10.1021/je5005593
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Aspects of Clathrate Hydrate Nucleation and Growth

Abstract: In this study we present results of our investigations on simple CH4-hydrate and mixed hydrates during the initial steps of the hydrate formation process. In situ Raman spectroscopy, microscopic observation and in situ X-ray diffraction were used in our systematic studies. Although these techniques give only a limited view on the molecular level the combined results from the experiments reported here indicate that the labile cluster hypothesis can describe the initial hydrate formation process. Specifically, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 30 publications
2
35
0
1
Order By: Relevance
“…The results indicate an enrichment of CO 2 in the secondary formed hydrate phase compared to the initial gas phase (23 mol% CO 2 and 77 mol% N 2 ). CO 2 is known as a good hydrate former, and the enrichment of CO 2 in the hydrate phase has already been reported in a different context elsewhere (Schicks & Luzi‐Helbing, ). Since N 2 is a small molecule and a comparably weak hydrate former (Sloan & Koh, ), the amount of N 2 encased in the hydrate phase is low compared to the amount of N 2 in the free gas phase.…”
Section: Resultsmentioning
confidence: 71%
“…The results indicate an enrichment of CO 2 in the secondary formed hydrate phase compared to the initial gas phase (23 mol% CO 2 and 77 mol% N 2 ). CO 2 is known as a good hydrate former, and the enrichment of CO 2 in the hydrate phase has already been reported in a different context elsewhere (Schicks & Luzi‐Helbing, ). Since N 2 is a small molecule and a comparably weak hydrate former (Sloan & Koh, ), the amount of N 2 encased in the hydrate phase is low compared to the amount of N 2 in the free gas phase.…”
Section: Resultsmentioning
confidence: 71%
“…These amorphous clusters are deemed precursors of nucleation of clathrate hydrates 41 . Their specific formation pathways are significantly affected by the size and solubility of guest molecules 42 , a finding that has been confirmed with macroscopic measurement methods including Raman spectroscopy and X-ray diffraction 43 . Furthermore, using MD simulations, Walsh et al .…”
Section: Introductionmentioning
confidence: 65%
“…For example, Schicks and Ripmeester 15 observed the coexistence of sI and sII hydrates formed from methane, ethane, and propane mixtures and Uchida et al 38 reported the coexistence of sI and sII hydrates formed from methane and propane mixtures. In recent work, Schicks and Luzi-Helbing 17 were also able to demonstrate the coexistences of sI and sH hydrates for a gas mixture of methane and FIG. 4.…”
Section: -29mentioning
confidence: 88%
“…A recent study reports the coexistence of sI and sH hydrates formed from a gas mixture of methane and 2-methylbutane. 17 Given these experimental observations, it would be interesting to identify the molecular mechanism of the possible structural a) Authors to whom correspondence should be addressed. Electronic addresses: liangshuai@ms.giec.ac.cn and pkusalik@ucalgary.ca interconversion and packing polymorphism between these crystalline phases; this is the focus of this study.…”
mentioning
confidence: 99%